Neutrophil NADPH Oxidase Is Reduced at the Anaplasma phagocytophilum Phagosome - IJdo, Jacob W. (American Society for Microbiology, 2004)
The intracellular organism Anaplasma phagocytophilum causes human granulocytic ehrlichiosis and specifically infects and multiplies in neutrophilic granulocytes. Previous reports have suggested that, for its survival, this bacterium suppresses the neutrophil respiratory burst. To investigate the mechanism of survival, we first assessed the kinetics of A. phagocytophilum entry into neutrophils by using double-labeling confocal microscopy. At 30, 60, 120, and 240 min of incubation, 25, 50, 55, and 70% of neutrophils contained bacteria, respectively. The neutrophil respiratory burst in the presence of A. phagocytophilum was assessed by a kinetic cytochrome c assay and by measurement of oxygen consumption. Neutrophils in the presence of A. phagocytophilum did not produce a significant respiratory burst, but A. phagocytophilum did not inhibit the neutrophil respiratory burst when phorbol myristate acetate was added. Immunoelectron microscopy of neutrophils infected with A. phagocytophilum or Escherichia coli revealed that NADPH oxidase subunits gp91(phox) and p22(phox) were significantly reduced at the A. phagocytophilum phagosome after 1 and 4 h of incubation. In neutrophils incubated simultaneously with A. phagocytophilum and E. coli for 30, 60, and 90 min, gp91(phox) was present on 20, 14, and 10% of the A. phagocytophilum phagosomes, whereas p22(phox) was present in 11, 5, and 4% of the phagosomes, respectively. Similarly, on E. coli phagosomes, gp91(phox) was present in 62, 64, and 65%, whereas p22(phox) was detected in 54, 48, and 48%. We conclude that A. phagocytophilum does not suppress a global respiratory burst and that, under identical conditions in the same cells, A. phagocytophilum, but not E. coli, significantly reduces gp91(phox) and p22(phox) from its phagosome membrane.